Neuroprotective effects of estrogens following ischemic stroke - Suzuki, Shotaro (2009)
Our laboratory has investigated whether and how 17β-estradiol (E(2)) protects the brain against neurodegeneration associated with cerebrovascular stroke. We have discovered that low, physiological concentrations of E(2), which are strikingly similar to low-basal circulating levels found in cycling mice, dramatically protect the brain against stroke injury, and consequently revealed multiple signaling pathways and key genes that mediate protective action of E(2). Here we will review the discoveries comprising our current understanding of neuroprotective actions of estrogens against ischemic stroke. These findings may carry far reaching implications for improving the quality of life in aging populations.